2021
DOI: 10.3390/toxins13090647
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Botulinum Toxin on Non-Motor Symptoms in Cervical Dystonia

Abstract: Patients with cervical dystonia (CD) may display non-motor symptoms, including psychiatric disturbances, pain, and sleep disorders. Intramuscular injection of botulinum toxin type A (BoNT-A) is the most efficacious treatment for motor symptoms in CD, but little is known about its effects on non-motor manifestations. The aim of the present study was to longitudinally assess BoNT-A’s effects on CD non-motor symptoms and to investigate the relationship between BoNT-A-induced motor and non-motor changes. Forty-fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 68 publications
1
16
0
Order By: Relevance
“…As cervical dystonia is associated with abnormally increased cerebellar connectivity with the sensorimotor cortex (5), the improvement of motor symptoms following the decrease in cerebellar connectivity after BoNT injections may be expected. Such an improvement is not seen in sleep disruption (52), which remains after repeated treatment. These data argue that although cerebellar overactivity could contribute to circadian dysfunction in dystonia, the pathways affected by BoNT are functionally and anatomically distinct from those involved in sleep, which is perhaps not unexpected, given that the BoNT injections are given at the focal peripheral sites where dystonia is manifest rather than as a systemic administration typical of oral or other parenteral forms of drug administration.…”
Section: Possible Mechanistic Interactions Between the Cerebellum Sle...mentioning
confidence: 87%
See 3 more Smart Citations
“…As cervical dystonia is associated with abnormally increased cerebellar connectivity with the sensorimotor cortex (5), the improvement of motor symptoms following the decrease in cerebellar connectivity after BoNT injections may be expected. Such an improvement is not seen in sleep disruption (52), which remains after repeated treatment. These data argue that although cerebellar overactivity could contribute to circadian dysfunction in dystonia, the pathways affected by BoNT are functionally and anatomically distinct from those involved in sleep, which is perhaps not unexpected, given that the BoNT injections are given at the focal peripheral sites where dystonia is manifest rather than as a systemic administration typical of oral or other parenteral forms of drug administration.…”
Section: Possible Mechanistic Interactions Between the Cerebellum Sle...mentioning
confidence: 87%
“…is challenging. Moreover, stress and anxiety, which are known to have unique relationships with sleep and the circadian system (150), are notable non-motor symptoms in dystonia that are typically unaddressed by common and often effective treatments like BoNT therapy (46,52). Another question to resolve emerged with the existence of mixed evidence regarding the prevalence of sleep disorders in dystonia; a study of 24 patients with both primary and secondary dystonia showed similar sleep organization and architecture relative to controls (151).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, the number of participants was relatively low, and differences in OMD subtypes were not considered; thus, the reliability remains uncertain. Apart from motor phenomena, there are other non-motor symptoms such as depression, anxiety, sleep problems, and pain in many patients with dystonia [ 28 , 29 , 30 , 31 , 32 ]. Non-motor symptoms are increasingly recognized as important determinants of HRQoL in cervical dystonia [ 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%